Enhancement of target specificity of CRISPR–Cas12a by using a chimeric DNA–RNA guide. Issue 15 (20th July 2020) - Kim, Hanseop; Lee, Wi-jae; Oh, Yeounsun; Kang, Seung-Hun; Hur, Junho K; Lee, Hyomin; Song, WooJeung; Lim, Kyung-Seob; Park, Young-Ho; Song, Bong-Seok; Jin, Yeung Bae; Jun, Bong-Hyun; et al.
Abstract: The CRISPR–Cas9 system is widely used for target-specific genome engineering. CRISPR–Cas12a (Cpf1) is one of the CRISPR effectors that controls target genes by recognizing thymine-rich protospacer adjacent motif (PAM) sequences. Cas12a has a higher sensitivity to mismatches in the guide RNA than does Cas9; therefore, off-target sequence recognition and cleavage are lower. However, it tolerates mismatches in regions distant from the PAM sequence (TTTN or TTN) in the protospacer, and off-target cleavage issues may become more problematic when Cas12a activity is improved for therapeutic purposes. Therefore, we investigated off-target cleavage by Cas12a and modified the Cas12a (cr)RNA to address the off-target cleavage issue. We developed a CRISPR–Cas12a that can induce mutations in target DNA sequences in a highly specific and effective manner by partially substituting the (cr)RNA with DNA to change the energy potential of base pairing to the target DNA. A model to explain how chimeric (cr)RNA guided CRISPR–Cas12a and SpCas9 nickase effectively work in the intracellular genome is suggested. Chimeric guide-based CRISPR- Cas12a genome editing with reduced off-target cleavage, and the resultant, increased safety has potential for therapeutic applications in incurable diseases caused by genetic mutations.